"Italians First": Workers on the Right Amidst Old and New Populisms. (3rd May 2018) - Zazzara, Gilda
Abstract: This article deals with the Italian working-class attitude to vote right-wing, seen in a long-term perspective, in particular in the northern and more industrialized regions. It stresses the fact that the left-wing parties reached their largest majority among working-class voters only for a short period. The end of the long cycle of factory conflicts of the 1970s on the one side, and the crisis of the "local political subcultures"—Catholic and Communist—in mediating the relationship between the working class and the central State on the other, marked the outbreak of a new political phenomenon: the establishment of the Lega Nord party in the 1980s. This party has been able to shift progressively from identity-based claims and secessionist proposals to xenophobia and the demand that a priority be accorded to Italian workers on the labour market. In the most recent years workers' support for the Lega Nord has been contended by a new populist competitor, the Five Star Movement, whose ability to intercept a widespread "working-class malaise" will be tested in years to come.